Sampling selection methodology: inventoried façades of Pelotas/RS (Research, Society and Development, 2020)
A sampling selection methodology using buildings facades of Pelotas/RS - a city located in the south of Rio Grande do Sul – are developed. Pelotas heritage is considered one of the most representative of eclectic architecture from Brazil. This sampling selection methodology alternative is based on framing, selection and buildings exclusion considering different solar orientations, typologies, damage degrees, among others. The properties list of Pelotas is presented in Cultural Heritage Inventory and Zona de Preservação do Patrimônio Cultural (ZPPC), following preservation level described in the City's III Master Plan. Some other constraints considering city morphology were also considering. Regarding the results, Pelotas mostly presents ground floor buildings, painted with mortar cover, and destined for services. Cracks, dirt and paint detachment were the main pathological manifestations found in Pelotas historical buildings. Although Pelotas presents many inventoried historic buildings protected by legal means, their cultural heritage condition recognition no guarantee the building's permanence over the time. Moreover, sampling methodology proposed in this study can enhance and systematize surveys in field studies and does not disqualify the properties. This development denotes an innovation to be certainly applied in other historic cities.